Persepsi Perawat terhadap Pelaksanaan Pendokumentasian Keperawatan di IRJ RSUP Fatmawati Jakarta - Ardiana, Anisah (Jurusan Keperawatan FIKES UNSOED, 2014)
Outpatient services is one of entrances of health services at the hospital. Generally, people considered the quality of hospital health care services based on the quality of outpatient care. Improving the nursing care quality of can be applied by implementing nursing care standard sice assessment to evaluation of the system through proper nursing care recording. This descriptive study involved 35 nurses as samples. Analysis was using frequency distribution. The instrument is a questionnaire consisting of four categories: definitions, he purposes, principles, and the importance of evaluating nursing documentation. Most of nurses perceive positively four categories of nursing documentation in outpatient of hospital. Generally nurses have good perception on implementing of nursing documentation, but not good on timeless principles. Improper perception will affect on unappropriate behavior to manager expectation. A manager should analyze factors that influence this perception including the factor of individuals themselves, a factor object (implementation of documentation) and work environment that support the implementation of nursing documentation in outpatient of hospital.